Functional Decision-Makers in the Departments of the Ministry of Youth and Sports from the Perspective of Employees - Khalaf, Yaseen; Rashid, Salam (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Objective: This study aimed to analyze the state of strategic renewal practices among decision-makers at the Ministry of Youth and Sports from the perspective of its employees. It also sought to examine the relationship between these practices and the effectiveness of operational performance. Methodology: The research adopted a descriptive-analytical method. A specially designed questionnaire, which measured four dimensions of strategic renewal, was administered to a stratified random sample of 150 employees. The instrument's validity and reliability were verified using factor analysis and Cronbach's Alpha coefficient. The data were then analyzed using SPSS software. Findings: The results showed that employees hold positive perceptions of strategic renewal practices, and that all four dimensions, strategic awareness, participation, change management, and continuous evaluation, are implemented at a high level. The study also revealed strong positive correlations among these dimensions, confirming that they function as an integrated system. Discussion: The findings support existing literature, which emphasizes that strategic renewal is essential for the public sector and that employee participation in this process reduces resistance to change. The results suggest the ministry has moved beyond traditional administrative inertia and has a solid foundation for continuous improvement. Conclusion: The research concludes that the Ministry of Youth and Sports has taken significant steps toward adopting strategic renewal. The key to sustainable success lies in enhancing strategic awareness and expanding employee participation. The study recommends leveraging these positive findings to build future action plans based on continuous evaluation and innovation.